(untitled) (New York, 2004)
This exciting new book for a growing market is the cutting- edge choice for PR courses. Global markets, new technologies and multiculturalism are covered throughout the book. This text is accompanied by a unique CD with video interviews of leaders in the PR field.
Keywords: Public relations,Quan hệ cộng đồng,Public relations; United States